Fucoidan-Rich Substances from Ecklonia cava Improve Trimethyltin-Induced Cognitive Dysfunction via Down-Regulation of Amyloid β Production/Tau Hyperphosphorylation - Seon Kyeong Park; Jin Yong Kang; Jong Min Kim; Seul Ki Yoo; Hye Ju Han; Dong Hwa Chung; Dae-Ok Kim; Gun-Hee Kim; Ho Jin Heo (Marine Drugs, 2019)
Ecklonia cava (E. cava) was investigated to compare the effect of polyphenol and fucoidan extract and mixture (polyphenol:fucoidan = 4:6) on cognitive function. The ameliorating effect of E. cava was evaluated using the Y-maze, passive avoidance and Morris water maze tests with a trimethyltin (TMT)-induced cognitive dysfunction model, and the results showed that the fucoidan extract and mixture (4:6) had relatively higher learning and memory function effects than the polyphenol extract. After a behavioral test, the inhibitory effect of lipid peroxidation and cholinergic system activity were examined in mouse brain tissue, and the fucoidan extract and mixture (4:6) also showed greater improvements than the polyphenol extract. Mitochondrial activity was evaluated using mitochondrial reactive oxygen species (ROS) content, mitochondrial membrane potential (MMP, ΔΨm), adenosine triphosphate (ATP) content, and mitochondria-mediated protein (BAX, cytochrome C) analysis, and these results were similar to the results of the behavioral tests. Finally, to confirm the cognitive function-related mechanism of E. cava, the amyloid-β production and tau hyperphosphorylation-medicated proteins were analyzed. Based on these results, the improvement effect of E. cava was more influenced by fucoidan than polyphenol. Therefore, our study suggests that the fucoidan-rich substances in E. cava could be a potential material for improving cognitive function by down-regulating amyloid-β production and tau hyperphosphorylation.